THE IMPORTANCE AND ROLE OF PREPOSITIONS IN ENGLISH GRAMMAR (Ustozlar uchun, 2026)
This article explains the importance and role of prepositions in English. Prepositions show the relationship between words in a sentence. They are used to express time, place, and direction. The article also mentions the difficulties learners face when using prepositions. In addition, it shows through examples how prepositions make sentences clearer and easier to understand. Using prepositions correctly improves communication. Overall, although prepositions are small words, they are very important in English.